Thirty-Day Results of the Novel CGuard-Covered Stent in Patients Undergoing Carotid Artery Stenting. (August 2021) - Tigkiropoulos, Konstantinos; Papoutsis, Ioakeim; Abatzis-Papadopoulos, Manolis; Kousidis, Panagiotis; Mpismpos, Dimitrios; Melas, Nikolaos; Stavridis, Kyriakos; Karamanos, Dimitrios; Lazaridis, Ioannis; Saratzis, Nikolaos
Objective: The aim of this study was to provide early-term evaluation, safety, and efficacy of the novel CGuard (Inspire MD, Tel Aviv, Israel) micromesh self-expanding stent with embolic protection system (EPS) during carotid artery stenting (CAS) procedure. Materials and Methods: All patients who underwent CAS with CGuard carotid stent system from January 2018 to September 2020 in a tertiary center were prospectively evaluated. Primary endpoints included technical success and perioperative neurological events (0–48 hours). Secondary endpoint was the rate of neurologic, cardiac events, and death (major adverse event or MAE) at 30 days. Patency of CGuard, peak systolic velocity (PSV), and end diastolic velocity (EDV) were evaluated at 30 days with duplex ultrasound. Results: A total of 103 patients underwent CAS procedure. Forty patients were symptomatic, and 63 patients were asymptomatic with stenosis greater than 70%. Technical success was 100%. Local anesthesia was applied in 94 patients (93%). Embolic protection devices were used in 6 patients (5.8%). Access site complications were 1.9%. Mean internal carotid artery stenosis diameter reduced from 79.47% to 14.68%. Two patients had transient ischemic attack (1.9%) and 1 patient experienced a cerebral hyperperfusion syndrome (CHS) perioperatively. External carotid artery (ECA) occlusion occurred in 1.9%. Four patients experienced jaw claudication (3.8%) postoperatively. Mean time of operation was 41 minutes. Mean duration of hospitalization was 3.1 days. The 30-day rate of MAE was 0%. CGuard patency was 100%, mean internal carotid PSV was reduced from 251.57 to 77.29 cm/s, and mean internal carotid EDV was reduced from 154.62 to 24.63 cm/s at 30 days. Conclusion: Our study shows that CGuard stent with EPS is an effective and safe device for treatment of carotid artery stenosis with acceptable low perioperative neurologic events, even with low embolic protection device usage. Larger multicenter and randomized studies are necessary to confirm its long-term efficacy.